Retinal Nerve Fiber Layer Thickness in Human T-cell Lymphotropic Virus Type 1 Patients. (2nd December 2017) - Merle, Harold; Hage, Rabih; Jeannin, Séverine; Cabre, Philippe; Olindo, Stéphane
ABSTRACT: Purpose : To determine whether there is an optic neuropathy (ON) in patients with human T-cell lymphotropic virus type 1 (HTLV-1) infection. Methods : We included HTLV-1 asymptomatic carriers (a.c.HTLV-1) and tropical spastic paraparesis/HTLV-1 associated myelopathy (TSP/HAM) patients between January 1st, 2014 and March 31st, 2015. All patients had complete eye examination. The visual acuity (VA) and retinal nerve fiber layer (RNFL) thickness were measured and compared to age- and sex-matched control groups including patients seen in our refraction clinic with no previous medical or surgical history. Results : Thirty-one a.c.HTLV-1 (group 1) and 29 TSP/HAM patients (group 2) were included. The average RNFL thickness was 99.9 ± 14.3 µm in group 1 and 87.8 ± 19.2 µm in group 2. The average RFNL thicknesses were lower in both groups, when compared to controls. The difference was significant in patients with TSP/HAM (87.8 ± 19.2 µm vs. 97 ± 7.8 µm; p = 0.003) who also had significantly decreased VA. Conclusions : We report here the first study about the RNFL thickness in patients with TSP/HAM. In these patients, there is decrease of the RNFL thickness with subtle but definite decrease of VA. This suggests that subclinical ON occurs in the natural history of the disease. The diagnosis of TSP/HAM must be evoked as a differential of primary progressive multiple sclerosis in a population at risk. Moreover, RNFL thinning with no evidence of glaucoma should raise suspicion for HTLV-1 infection and TSP/HAM in a population at risk.